Marco Lucchesi: por uma educação literária transformadora - Almendra, Viviani Aparecida Zornetta (2023)
This dissertation enquires into the importance of reading literature when it comes to the formation/transformation of individuals, especially teachers, who, in addition to the demand of becoming steady readers, should communicate the importance of literature to their students. One of the virtues of literature is that it can transport us to other possible, imaginary worlds solely through the power of words. It excites our senses, nourishes our dreams, awakens our curiosity, stimulates our creativity, enabling us to find creative solutions to the challenges and difficulties of life. Literature provides us with lines of flight that enable us to free ourselves from excruciating social pressures, thus contributing, according to Paulo Freire, to a humanizing and emancipatory praxis. Making a case for the self-transformative virtue of reading literature, and with life-altering power as our premise, we believe that great literary works such as Marco Lucchesi’s, whose writing stands out for its poetic beauty, interdisciplinarity, and stylistic diversity, in addition to its historical rigor and commitment to the humanistic formation of its readers, can provoke the senses of teachers and students and invite them to enjoy the (trans)formative education based on the power of literature. To demonstrate the (trans)formative and humanizing virtue of Lucchesi’s literature, we rely on the theoretical contributions of various authors such as Paulo Freire, Gilles Deleuze and Félix Guattari, Ana Maria Haddad Baptista, Judite Zamith-Cruz, and on the essential critical heritage about Lucchesi, of which we highlight the works of Diana Navas, Marcia Fusaro, Montserrat Villar González, Ana Miranda and Clivia Cainelli. This dissertation is divided into three chapters: in Chapter 1, we make a brief presentation of the history of reading, besides discussing the importance of reading, arguing about the role of e-books in the development of reading skills, and assessing the importance of reading literature; in Chapter 2, we introduce the works and philanthropic actions carried out by Marco Lucchesi, who, in addition to his engagement in a wide variety of social causes, creates literature capable of flourishing our individual and social skills, offering us knowledge to navigate the world. In Chapter 3, based on the qualitative methodology that guided this research, we analyze the information obtained in semi-structured interviews carried out with 3 educators who, in addition to being attentive readers of Lucchesi’s literature, have developed educational projects alongside students and other teachers to promote the habit of reading literature, particularly Marco Lucchesi's books (thus proving the great potential of his works for literary education programs that could be implemented in Brazilian schools and universities). The theoretical course of this dissertation allowed us to validate the importance that literary reading has in the lives of individuals. On the other hand, we also concluded that, if literary education remains captive of prejudice and orthodoxies, it will only keep students away from books and compromise the educational results expected. We also concluded, based on the presentation of these educational projects, that great literature such as Lucchesi’s could and should be taught in Brazilian schools, which is presently lacking content that provokes us to go beyond conformism and inertia.